Poverty, Forest Dependence and Migration in the Forest Communities of Turkey : Evidence and Policy Impact Analysis - World Bank Group (World Bank, Washington, DC, 2017)
This paper is part of an ongoing collaboration between the World Bank and the General Directorate of Forestry (GDF) in Turkey. In 2013, the GDF requested that the World Bank help update their 5-year Forest Sector Strategy (2017-2021), and together they developed a Forest Policy Note (FPN) which provided a comprehensive overview of the Forestry Sector; an in-depth analysis identifying areas in which the sector could adopt international best practices in sustainable forestry management. As part of that analysis, this PROFOR-funded survey was undertaken to better understand the socioeconomic dimensions of forest villages, their forest dependency, and constraints to income growth in rural areas. The survey collected important information on the socio-economic conditions of forest village populations, income generating opportunities, forest use and management practices, migration and activities of forest development programs and cooperatives. The analysis highlights the main challenges to improving villager livelihoods and forest management and provides much needed evidence for informing the design and implementation of forest community development programs.